BERBER IN THE TEXTS OF THE ALGERIAN CONSTITUTIONS. ANALYSIS OF DISCURSIVE PRACTICES. DISCURSIVE AND JURILINGUISTIC APPROACHES - BOUKHERROUF, Ramdane (Comparative Legilinguistics, 2019)
Our contribution consists in analyzing the discursive practices of the three Algerian constitutional texts (1996, 2002, and 2016) dedicated to the constititionalisation of the Amazigh language. It is about showing and putting in evidence, through a textual and pragmatic analysis of these texts, the status and the definition that has been scattered over the national territory. To carry out our analysis, we will mainly appeal to the field of jurilinguistics. Moreover, the Amazigh language is defined in the constitution as a set of certified varieties throughout the national territory.